Análise do Mapa da Cadeia de Valor em um Hospital do Vale do Paraíba - Gouvêa, Pedro Henrique Rivera [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The Lean Thinking is a method used by various industries in order to eliminate waste and ensure quality for the customer. In the current scenario, Lean has been used in other areas such as the hospital in which many tools are being adopted in order to improve its internal processes. One such tool is the Value Stream Mapping, which proved to be an effective tool in industrial environments, and is being adopted by several hospitals. Thus, this paper presents a case study on the use of this tool in a sector of a hospital in the Vale do Paraíba, evaluating its importance, its impacts, positive and negative points and future projections. This is in the context of Lean Healthcare, a new model based on the principles of Lean Thinking which has been adopted by several hospitals and clinics throughout Brazil successfully
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho; Eficiencia industrial; Eficiencia organizacional